Entropic Mapping and Green’s Function Approximation for Electrostatic Field with Dirichlet Boundary Conditions - Urniezius, R.; Siozinys, V. (Elektronika ir Elektrotechnika, 2013)
This paper presents entropic updating approach to find the mirror charge, which is induced in the bounded region of the electrostatic field of a single source image. We analyze two sample scenarios with Dirichlet boundary conditions. The first scenario is two spheres with matching centre and the unit charge in between those spheres. The second scenario is a sphere and a plane. Experimental results show that there is no need to have more than N=6 steps to find an acceptable Green’s function approximation for the electrostatic field of interest. Additionally, the scenario with two spheres shows similar convergence results when compared with eigenfunction expansion. DOI: http://dx.doi.org/10.5755/j01.eee.19.1.3249